Nordic Drone: Pedal points and static textures as musical imagery of the northerly environment - Juha Torvinen; Susanna Välimäki (Routledge, 2022)
Musical imagery that somehow references the environment is extremely common in works by Nordic composers, both past and present. Some pieces are given titles, programmes or performance contexts that directly refer to the local environment, its natural phenomena, landscape (be it concrete or mythical) or atmosphere; others suggest more conventional musical imagery, such as topics, allusions, inter-textuality and structural tropes. Many more seem to convey or evoke in a more abstract and experiential way an acute sensitivity to the environment, like ambient music for instance. One of the most common ways in which Nordic music evokes its environment is through the use of static musical textures: barren pedal points, drones, stable chords, clusters or sound masses, and other long-lasting or repetitive gestures, combined with hushed, muted and often dark timbres. Such textures seem to suggest a mode of subjectivity beyond individuality or agency. This makes static textures a topical case to study not only from the point of view of hermeneutics and phenomenology, but also as a significant trend of contemporary aesthetics in Nordic music, related to the ecological turn of twenty-first century art. It is precisely this ‘Nordic drone’ that we aim to elucidate in this article by analysing examples of classical music of the Nordic countries from the twentieth and twenty-first centuries that use static textures, pedal points and other repetitive imagery to induce a sense of nature, environment, space and place.
First follows a historical introduction that briefly discusses Finnish music of the early 20th century. Then follows more detailed case studies of Finnish and Icelandic contemporary music, by Erik Bergman, Kaija Saariaho, and Anna Thorvaldsdottir. Methodologically, the approach draws on cultural music analysis, ecomusicology and (eco)philosophy.
Finland and Iceland, occupying geographical border zones of the Nordic region, have produced a rich repertoire of music that is characterised by various kinds of static textures. Therefore, this repertoire can exemplify the topical and global significance of Nordic music in today’s world with respect to its ability to reflect, construct and scrutinize the relationship between the individual and the environment, and between humanity and nature in general.
The Nature of Nordic Music